Proposed upgrading of Galaxy Inn Hotel for Galaxy Inn Hotel Sdn. Bhd. at No PT 4148 & 4149, Jln Sultan Idris Shah 32200 Lumut, Perak / Nur Anis Syazwani Mohd Faudzi - Mohd Faudzi, Nur Anis Syazwani (Faculty of Architecture, Planning and Surveying, 2012)
The final project for the student of diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to Proposed Upgrading of Galaxy Inn Hotel at No. PT4148 & 4149, Jln. Sultan Idris Shah 32000 Lumut, Perak Darul Ridzuan. This proposed Boutique Hotel is to fulfill the Galaxy Inn Hotel mission and vision to create the hotel where people can go and get comfortable environment. The building environment is designed to bring people together into natural gathering places where chance encounters can stimulate new ideas. The space itself is a physical counterpoint to the aesthetic problems that designers are solving. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the clients itself. Connected to that, the chosen design style for Galaxy Inn Hotel is based on urban nice style, but still apply the casual modern style and at the same time would bring with different image that user would only get in Galaxy Inn Hotel. Before getting design, that is suitable with the client’s needs, some data analysis should be done where these analysis is on types of visitors attend the session, types of services offered, spaces to be concluded in the proposed area, and operation time.